Propria manu. Om Erasmus af Rotterdams testamente og hans efterladte papirer - Petersen, Erik (Fund og Forskning i Det Kongelige Biblioteks Samlinger, 2014)
NB: Artiklen er på dansk, kun resuméet er på engelsk.MSS GKS 95 2°, GKS 96 2° and Thott 732° in the RL are among the most remarkable sources in the library’s collections. The nearly 900 folia contained in the volumes represent the literary Nachlass of Erasmus of Rotterdam as it was left by him at his death close to midnight between the 11th and 12th of June 1536. No clue to how this material has come to Denmark has yet come to light. In the present contribution the author gives a brief survey of what is known about the history of the volumes. The aim is to establish a basis for new research into the later history of the manuscripts by looking into the dispositions that were made concerning the papers while still in Basel, and to discuss how the papers were kept by Erasmus himself and managed by his heir, friends and assistants after his death. GKS 95 2° was first recorded in a RL catalogue signed and dated by the librarian, Willum Worm, on the 4th of January 1671. The terminus post quem of accessions recorded in this source which has been quoted as Catalogus Schumacheri cannot, as has previously been assumed, be fixed to the year 1663. GKS 96 2° is first recorded in a RL catalogue in 1729. Thott 732° was included in the RL after the death of count Otto Thott in 1784, and first recorded in the printed Index codicum manuscriptorum, in volume 7 of the Bibliotheca Thottiana from 1795. The presence of this rich autograph material in the RL remained unnoticed by scholars until P.S. Allen published a survey of GKS 95 2°, The Copenhagen Manuscript, as Appendix XIII of Opus Epistolarum in 1913. And it was only when C. Reedijk had published his study Three Erasmus Autographs in the Royal Library at Copenhagen in 1966 (in Festschrift Herman de la Fontaine Verwey) that it became known to Erasmus-scholars that the material in Copenhagen included two more volumes, an addition of more than 1200 manuscript pages in the hand of Erasmus. Erasmus did not give any instructions concerning his literary Nachlass in his last will of 12 February 1536. Nor did he bequeath it to someone. He had sold his library to Jan Laski already in 1525, on the conditions that it remained at his disposal until his death. An analysis of the extant list of books in the library shows that it included manuscripts, and Laski’s correspondence with Bonifacius Amerbach after Erasmus’ death discloses that Laski also acquired manuscripts, not in the list, which he had noticed while staying with Erasmus in Basel, amongst them the famous codex Arcerianus now in Wolfenbüttel. According to the list, the library bought by Laski included one manuscript containing a text of Erasmus, but he did not acquire the Nachlass contained in the volumes in Copenhagen. Laski’s errant life did, in fact, bring him to Denmark in 1553. He and his reformed community had been forced to leave London, and he asked the Danish king for asylum. Most likely he brought his library along, and Erasmus’ books thus may have been in Denmark for a few weeks. Nothing was left there, neither manuscripts nor printed books. The RL has only a single book that may have belonged to Erasmus, but this volume was not included in the list of items acquired by Laski from Erasmus. Erasmus’ library was sent to Laski in Krakow soon after the death of Erasmus. His literary Nachlass remained in Basel. Although it is not stated explicitly in the will, it must have become the property of Bonifacius Amerbach, the main heir, to whom Erasmus bequeathed whatever in his possession had not been given to others. Since the Nachlass is not bequeathed to anybody in the will, it must have been included in the gifts to Amerbach. Its presence in Basel is also attested by two copies of Erasmus’ will, one added to the papers in Thott 732°, another added to the papers in GKS 95 2°. Both were copied from the original will in Erasmus’ own hand which remained with Amerbach. These copies offer an important clue to what happened to the Nachlass after Erasmus’ death. The copy of the will in Thott 732° was made by Nicolaus Episcopius, as is evident both from the handwriting and his signature. The copy in GKS 95 2° is not signed. It was not copied by Gilbertus Cognatus, as maintained by Reedijk. Palaeographical and chronological details do not favour such an identification, and in addition the copy contains faults more grave than one would expect from an experienced copyist and able latinist such as Cognatus. In his Appendix XIII P.S. Allen described GKS 95 2° as “a congeries brought together almost haphazard by some one desirous of gathering and yet hardly heeding what he gathered”, and proposed a theory about how the paper contained in the volume was brought together: “This orderly and yet disordered arrangement is just what might be expected in a collection hurriedly gathered during the necessary dispositions which follow death.” C. Reedijk supported Allen’s theory and found it valid also in relation to MSS GKS 96 2° and Thott 732°. In my opinion both of them stressed the disorder of the papers too much and misinterpreted their context before and after Erasmus’ death. In fact, Erasmus had had the papers in his hands less than half a year before he passed away. As he writes in his letter ‘to the friendly readers’ which he dated on 20 February 1536 (ep. 3100) it was his plan to go through what he described as schedarum mearum confusissimos acervos. His intention was to remove and destroy manuscripts in order to prevent others from publishing them after his death, or even while he was still alive, as had happened more than once before. He also looked for letters that might be suitable for publication. This took place only 8days after he had written his last will and was clearly part of his preparations for death. The rich contents of the manuscripts in Copenhagen seem to indicate that he destroyed little, if anything. The process of going through the papers has given him an opportunity to put them in a slightly better order than previously, and he seems to have used it. The letter to the friendly readers itself was placed on top of a pile with drafts of letters that is still kept together in GKS 95 2°. After Erasmus’ death Amerbach meticulously fulfilled Erasmus’ instructions as formulated in his will. Since there were no instructions concerning the literary Nachlass, he made his own decision and gave the papers now included in Thott 732° to Nicolaus Episcopius who added his own copy of the will – and a note of his ownership which is now heavily damaged and only readable in part. Reedijk interpreted the poor remnants thus: Nicolai Episcopii, succesoris <Io. Frob.> et Justinae <filiae> D <Erasmi mo>numentum Rot<erodami> <………>. Less daring I have been able to decipher only the following with certainty: Nicolai Episcopii, succesor… / numentum hoc. That leaves us with Episcopius’ name in the genitive and monumentum hoc, just enough to assure that it did in fact belong to him and that he valued it highly. GKS 95 2° does not contain any remains of a similar note. As stated above, the copy of the will in this volume is not in the hand of Cognatus. Nor has it been copied by Hieronymus Frobenius, but I believe I have found one small element that might link it to his family or a person in his workshop. In the name Desiderius Erasmus Roterodamus at the very beginning of the will Erasmus has been written with an added i: Erasmius. Really an odd fault at a very visible location, perhaps a kind of Freudian slip committed by someone who knew a person of that name – or indeed was named Erasmius himself, such as Hieronymus’ younger brother, Erasmius Frobenius, Erasmus’ beloved godson. This is not much of a lead, but perhaps sufficient to suggest that the volume belonged to Hieronymus Frobenius, given to him as a gift in memory of Erasmus by Amerbach. The third volume, GKS 96 2°, contains no copy of the will, no notice of an owner, and no traces that may point to one. But perhaps exactly the absence of such traces points to Amerbach himself. If nature had entrusted him with sensibility enough to know that a volume of Erasmus’ autographa would exhilarate his friends and companions as executores testamenti, it is easy to understand why he decided to keep one for himself. And as to the will, Amerbach needed no copy. He possessed the original document, the ultima voluntas as recorded on the 12th of February 1536 by Erasmus himself, propria manu.